Electron currents and heating in the ion diffusion region of asymmetric reconnection. Issue 10 (18th May 2016) - Graham, D. B.; Khotyaintsev, Yu. V.; Norgren, C.; Vaivads, A.; André, M.; Lindqvist, P.‐A.; Marklund, G. T.; Ergun, R. E.; Paterson, W. R.; Gershman, D. J.; Giles, B. L.; Pollock, C. J.; et al.
Abstract: In this letter the structure of the ion diffusion region of magnetic reconnection at Earth's magnetopause is investigated using the Magnetospheric Multiscale (MMS) spacecraft. The ion diffusion region is characterized by a strong DC electric field, approximately equal to the Hall electric field, intense currents, and electron heating parallel to the background magnetic field. Current structures well below ion spatial scales are resolved, and the electron motion associated with lower hybrid drift waves is shown to contribute significantly to the total current density. The electron heating is shown to be consistent with large‐scale parallel electric fields trapping and accelerating electrons, rather than wave‐particle interactions. These results show that sub‐ion scale processes occur in the ion diffusion region and are important for understanding electron heating and acceleration. Key Points: The ion diffusion region of asymmetric reconnection is investigated Electron‐scale currents develop in the ion diffusion region Electron heating is consistent with electron trapping by DC electric fields